2005
DOI: 10.1021/ie058017j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Microwave Irradiation on the Mass-Transfer Kinetics of Propylbenzene in Reversed-Phase Liquid Chromatography

Abstract: The effect of microwave irradiation on the kinetics of mass transfer in reversed-phase liquid chromatography (RPLC) was studied by measuring its influence on the band profile of propylbenzene in a C 18 -silica column eluted with an aqueous solution of methanol and placed inside a microwave oven. The elution peaks were measured by the pulse-response method, under linear conditions. The amount of microwave energy induced into the column was varied based on the microwave input power. The experimental data were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This phenomenon disappears as the radiation ceases.As a result of all these processes, the intraparticle and the surface diffusivity coefficients are higher in presence than in the absence of the microwave field. 10 In the present study already for thiamine, narrower peaks were obtained when the microwave field was on, in spite of the fact that the mobile phase heating was negligible (i.e., a 2 C increase in the temperature was noticed). Additional processes such as the effect of microwave on the ionization of the stationary phase could be considered as negligible because perchloric acid was present in the mobile phase.…”
Section: Studies Under Isothermal Conditionsmentioning
confidence: 39%
See 1 more Smart Citation
“…This phenomenon disappears as the radiation ceases.As a result of all these processes, the intraparticle and the surface diffusivity coefficients are higher in presence than in the absence of the microwave field. 10 In the present study already for thiamine, narrower peaks were obtained when the microwave field was on, in spite of the fact that the mobile phase heating was negligible (i.e., a 2 C increase in the temperature was noticed). Additional processes such as the effect of microwave on the ionization of the stationary phase could be considered as negligible because perchloric acid was present in the mobile phase.…”
Section: Studies Under Isothermal Conditionsmentioning
confidence: 39%
“…As the temperature increase was more remarkable at 84 W than at 21 W, the drop in system pressure was also more significant (Fig.2c).Fig.3shows that the retention factor decreased with the MW applied power for biotin and riboflavin. The reason that can be argued to explain this trend was that the diffusivity of the analyte increased because the radiation improved this physical property10 and the mobile phase temperature rose (with a concomitant decrease in the viscosity) as a result of the absorption of microwave radiation. Another interesting observation was that the modification in retention times with MW application depended on the evaluated vitamin.…”
mentioning
confidence: 99%
“…The last type of heating under MW can be attributed to magnetic loss occurring in magnetic materials, as Fe, Ni and Co, affected by both electric field and magnetic field, and some metal oxides such as ferrites or nickel oxides 237 . Finally, it was demonstrated that there can be a positive, but non-thermal, effect of microwaves on the intra-particle diffusion and mass transfer coefficients in surface modified porous silica due to the molecular excitation of organic molecules with a higher dielectric loss than the aqueous solution 238 .…”
Section: Generalitiesmentioning
confidence: 99%
“…237 Finally, it was demonstrated that there can be a positive, but nonthermal, effect of microwaves on the intraparticle diffusion and mass transfer coefficients in surface modified porous silica due to the molecular excitation of organic molecules with a higher dielectric loss than the aqueous solution. 238 Consequently, MW irradiation can be an efficient way for wastewater treatment due not only to the heating of water or polar pollutants but more importantly to possible beneficial interactions with oxidants and catalysts. In fact, the direct treatment of wastewater under MW irradiation leads to an increase in temperature, which causes the removal from water of volatile or semivolatile pollutants by evaporation but is not sufficient for breaking chemical bonds and decompose organic pollutants.…”
Section: From Fundamentals To Practical Improvements In Catalytic Pro...mentioning
confidence: 99%
“…In addition, microwave-specific effect (non-thermal effect) may further enhance the intra-particle diffusion and mass transfer coefficients in a heterogeneous system (Galinada et al 2005;Galinada and Guiochon 2007), which may facilitate the persulfate oxidation of soil-sorbed organic contaminants. As there is no reported application of microwave-activated persulfate for in situ subsurface remediation, this study aimed to evaluate the potential of microwave-activated persulfate for subsurface remediation.…”
Section: Introductionmentioning
confidence: 99%